Local impacts of a global crisis: Food price transmission and poverty impacts in Ghana - Cudjoe, Godsway; Breisinger, Clemens; Diao, Xinshen (International Food Policy Research Institute, 2008)
This paper takes a local perspective on global food price shocks by analyzing food price transmission between regional markets in Ghana. It also assesses the impacts of differential local food price increases on various household groups. Taking the recent global food crisis as an example, we find that prices for domestic staples within all regional markets are highly correlated with prices for imported rice. However, price transmission between pairs of regional markets is limited; it is complete for local rice and maize only when more rigorous cointegration analysis is applied. Our findings also show the important role of seasonality in the determination of market integration and price transmission. The welfare effect for households as consumers appears relatively modest at the aggregate national level due to relatively diverse consumption patterns. However, the national average hides important regional differences, both between regions and within different income groups. We find that the poorest of the poor—particularly the urban poor—are the hardest hit by high food prices. The negative effect of the food crisis is particularly strong in the north of Ghana. Different consumption patterns, in which grains account for a larger share of the consumption basket in the north compared to the rest of the country, together with much lower initial per capita income levels, are the main explanations for this regional variation in the price effect.